Hermeneutika Teks Lirik Lagu “Tapi Diterima” Karya Nadin Amizah (Tinjauan Hans-Georg Gadamer) - Ramaya Octavia Dewi Anjania; Haerussaleh Haerussaleh; Afan Faizin (Jurnal Pendidikan Bahasa dan Sastra Indonesia Metalingua, 2026)
This study is motivated by the understanding that song lyrics can be treated as literary texts that contain symbols and open up space for interpretation. Nadin Amizah's album Untuk Dunia, Cinta, dan Kotornya (For the World, Love, and Filth) presents reflective lyrics that represent human experiences in various symbolic fields. This study aims to examine the construction of symbolic fields in the song “Tapi Diterima” as part of the album's horizon of meaning through Hans-Georg Gadamer's hermeneutic approach. This study uses a descriptive qualitative method with library research techniques. The object of research is the lyrics of the song “Tapi Diterima,” which are treated as symbolic texts and analyzed in relation to the overall meaning of the album. The analysis process is carried out through hermeneutic reading by limiting the interpretation to the horizon of the text, without explicitly involving the empirical reader's horizon or the author's intention. In this position, the researcher is positioned as an explicit reader who enables the understanding of the meaning offered by the text. The results of the study show that the song “Tapi Diterima” constructs a symbolic field composed of dominant symbols and supporting symbols that are internally related. This symbolic field represents existential and relational experiences that are understood as part of a coherent meaning structure in the album Untuk Dunia, Cinta, dan Kotornya. Thus, symbolic meaning is understood as the result of a dialogue between the meaning structure in the text and the process of understanding enabled by the text itself.